Quercus hemisphaerica, Darlington Oak - Melissa H. Friedman; Michael G. Andreu; Heather V. Quintana; Mary McKenzie (EDIS)
FOR 239, a 2-page fact sheet by Melissa H. Friedman, Michael G. Andreu, Heather V. Quintana, and Mary McKenzie, describes this deciduous tree found along sandy ridges and mixed forests from Virginia south to Florida and west to Texas — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.